Cuscuta reflexa invasion induces Ca2+ release in its host - Albert, Markus; Van Der Krol, S.; Kaldenhoff, R. (Plant Biology, 2010)
Cuscuta reflexa induces a variety of reaction in its hosts. Some of these are visual reactions, and it is clear that these morphological changes are preceded by events at the molecular level, where signal transduction is one of the early processes. Calcium (Ca2+) release is the major second messenger during signal transduction, and we therefore studied Ca2+ spiking in tomato during infection with C. reflexa. Bioluminescence in aequorin-expressing tomato was monitored for 48 h after the onset of Cuscuta infestation. Signals at the attachment sites were observed from 30 to 48 h. Treatment of aequorin-expressing tomato leaf disks with Cuscuta plant extracts suggested that the substance that induced Ca2+ release from the host was closely linked to parasite haustoria. © 2010 German Botanical Society and The Royal Botanical Society of the Netherlands.
CRIS-Team Scopus Importer:2020-03-09
Keywords: Aequorin; Cuscuta reflexa; Parasitic plants; Tomato